2015
DOI: 10.1080/00273171.2014.963193
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Real and Artifactual Moderators of Effect Size in Meta-Analysis

Abstract: This article argues that while meta-analytic studies are widely used in psychological literature, heterogeneity and the potential for confounding remain major problems in the interpretation of meta-analytic study results. The article demonstrates the use of exploratory analysis including graphical methods prior to meta-analysis, and introduces a methodology to screen for artifactual effects. These procedures are illustrated on effect size data comparing depression treatment outcome from psychotherapy versus ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…While causal conclusions cannot be drawn from these associations, it does appear to be the case that, in the Figure 1. Efficiency ratios calculated on the studies identified by Collins and Carey (2015) and averaged across year of publication. This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Problems With Relying Solely On Randomized Controlled Trialsmentioning
confidence: 99%
See 3 more Smart Citations
“…While causal conclusions cannot be drawn from these associations, it does appear to be the case that, in the Figure 1. Efficiency ratios calculated on the studies identified by Collins and Carey (2015) and averaged across year of publication. This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Problems With Relying Solely On Randomized Controlled Trialsmentioning
confidence: 99%
“…The efficiency of treatments is also decreasing over time. Using the studies from Collins and Carey (2015), efficiency ratios (Carey, Tai, & Stiles, 2013) were conducted on all studies that provided effect size and number of sessions data. These ratios were averaged for studies that were published in the same year.…”
Section: Problems With Relying Solely On Randomized Controlled Trialsmentioning
confidence: 99%
See 2 more Smart Citations